Construction safety engineering principles : - MacCollum, David V. (Mcgraw-Hill, 2007)
Construction Safety Engineering Principles: Designing & Managing Safer Job Sites equips architects, engineers, and construction managers with a step-by-step methodology for identifying and controlling hazards before construction starts. The book explains how to look beyond the utility of machinery and equipment to how they will actually be used on a construction site_and thereby spot potential hazards in advance. Construction Safety Engineering Principles enables construction professionals to: Design and plan safer construction sites for residential, commercial, and industrial projects; correct safety problems before construction begins; dramatically reduce costly worker injuries and job delays and increase productivity and create a more cost-effective project.